2020
DOI: 10.1055/a-1088-5467
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Joint Stress during Running with Added Load in Females

Abstract: Patellofemoral joint (PFJ) pain syndrome is a commonly reported form of pain in female runners and military personnel. Increased PFJ stress may be a contributing factor. Few studies have examined PFJ stress running with added load. Our purpose was to analyze PFJ stress, PFJ reaction force, quadriceps force, knee flexion angle, and other kinematic and temporospatial variables running with and without a 9 kg load. Nineteen females ran across a force platform with no added load and 9.0 kg weight vest. Kinematic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…PF axial radiographs at different knee exion angles can well re ect the effects of weight-bearing dynamics on the alignment of the anterior PF region in vivo. Although several studies have suggested that the PF joint stress contact surface is mainly centered on the lateral compartment of the PF joint [12,34,35], some studies support the results of weight-bearing position knee dynamics studies that support that the PF joint stresses are on the medial PF surface. The study by Bhushan et al used an in vivo study using weight-bearing position dynamics MRI to understand PF joint movement patterns, and he concluded that the PF joint contact center point and peak strain location during motion is located medial to the femur and patellar cartilage [36].…”
Section: Resultsmentioning
confidence: 90%
“…PF axial radiographs at different knee exion angles can well re ect the effects of weight-bearing dynamics on the alignment of the anterior PF region in vivo. Although several studies have suggested that the PF joint stress contact surface is mainly centered on the lateral compartment of the PF joint [12,34,35], some studies support the results of weight-bearing position knee dynamics studies that support that the PF joint stresses are on the medial PF surface. The study by Bhushan et al used an in vivo study using weight-bearing position dynamics MRI to understand PF joint movement patterns, and he concluded that the PF joint contact center point and peak strain location during motion is located medial to the femur and patellar cartilage [36].…”
Section: Resultsmentioning
confidence: 90%
“…The full text of 227 studies was retrieved and screened (figure 2). In total, 71 articles were included in the systematic review 25–95. There were 63 within-subject studies (56 healthy individuals, 7 patellofemoral pain), 1 randomised controlled trial in healthy individuals (online supplemental table 2) and…”
Section: Resultsmentioning
confidence: 99%
“…We identified 27 studies that reported PFJRF during running 25 26 34 35 38 39 50 52 56–59 61 68 69 74–76 78 80–82 87 90 91 93 94. Pooled peak PFJRF in healthy individuals was 5.2±1.2 BW25 35 38 39 52 56–58 61 68 74 80–82 87 90 94 based on 17 studies and 4.1±0.9 BW in individuals with patellofemoral pain34 38 78 based on three studies during running (figure 3). The average running speed ranged from 2.33 m/s to 4.47 m/s in healthy individuals and 2.77 m/s to 4.00 m/s in individuals with patellofemoral pain.…”
Section: Resultsmentioning
confidence: 99%
“…That would be sustained through the mean angulation of women in pain (G1), which is very close to the borderline value of 15 degrees given as normal. In addition to that, biomechanical studies show that an accentuated femoral anteversion is associated with bigger movements of the dynamic valgo, which results in a bigger risk for PFPS 5,6,10,11 . A study 5 used CT measurements to validate Craig's test and found that the femoral neck angulation evaluated by this test may partially be the true anteversion angulation, as other factors may influence its value, even though the test has important clinical significance.…”
Section: Discussionmentioning
confidence: 97%